Verification of Equivalent-Results Methods - Leino, Rustan; Müller, Peter (Proceeding: ESOP'08/ETAPS'08 Proceedings of the Theory and practice of software, 17th European conference on Programming languages and systems, 2008)
Methods that query the state of a data structure often return identical or equivalent values as long as the data structure does not change. Program verification depends on this fact, but it has been difficult to specify and verify such equivalent-results methods and their callers. This paper presents an encoding from which one can determine equivalent-results methods to be deterministic modulo a user-defined equivalence relation. It also presents a technique for checking that a query method returns equivalent results and enforcing that the result depends only on a user-defined influence set. The technique is general, for example it supports user-defined equivalence relations based on Equals methods and it supports query methods that return newly allocated objects. The paper also discusses the implementation of the technique in the context of the Spec# static program verifier.